ANALISIS GAYA KEPEMIMPINAN HUMAN CAPITAL MANAGAMENT (HCM) MANAGER DAN STORE MANAGER DALAM MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN PADA MAXCELL DEPO TEKNIK DAN BANGUNAN - wa oca, Wa oca; amir, muh; abdullah, akhyar (Business UHO: Jurnal Administrasi Bisnis, 2017)
This study aims to determine the leadership style applied by Human Capital Management (HCM) Manager and Store Manager and employee work productivity at Maxcell Depot of Engineering and Building, Jl. Brig. Gen. M. Yoenoes. The formulation of the problem in this study is how the leadership style of Human Capital Management (HCM) Manager and Store Manager at Maxcell's Depot of Engineering and Building. With this type of field research, the research subjects were managers and employees, collecting data by using observation, interview and documentation techniques. Analysis of the data used according to Miles and Hubeman in M. Idrus's book consists of data reduction, data presentation and conclusion, using data validity techniques to carefully and openly record and document data, transparency about procedures in the field and things revealed and compare the things achieved through interview and observation methods, and examine the subjects so that the data produced is curate.The results of the study show that participatory and democratic leadership styles are the most dominant type applied by managers, but also not only apply that type but also apply some of the other leadership styles such as delegative leadership and paternalistic leadership style, only those two leadership styles does not involve employees / subordinates but is represented by the head of the division or head of each department. The forms of work productivity that appear are knowledge that increases because the company provides freedom for employees to develop knowledge or potential that exists within employees and work skills that are getting better because of the company also burn them with product knowledge and understanding of services, and attitudes that based on 8 corporate cultures and requires employees to follow or implement them